Pengaruh Desain Produk Dan Promosi Terhadap Keputusan Pembelian Motor Matic Honda Beat Di Kecatamatan Sananwetan Kota Blitar - Riffad Febriansyah; Sunan Trioko; Winarto Winarto (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
The need for vehicles for the Indonesian people is increasing with increasing mobility and increasing people's economic status as well as the ease of credit provided by banks and existing financing institutions making it easier for people to own them. This gives the company a great opportunity to further develop its sales not only in big cities but also in regions and regencies. Various kinds of motorbike brands have sprung up, many motorbike manufacturing factories are competing to create and make products to meet the needs of their consumers. Several well-known motorcycle brands in Indonesia come from the land of the rising sun such as Honda, Yamaha, Suzuki and Kawasaki. The purpose of this study was to: find out whether product design and promotion influence the decision to purchase a Honda Beat automatic motorbike in Sananwetan District, Blitar City. The objects in this study were all the people of the Sananwetan sub-district, taking samples from this study using the slovin formula and obtaining a sample of 100 people from 53,555 populations. This study uses a quantitative approach with primary data sources and secondary data. The results showed that product design and promotion had no significant effect on purchasing decisions for Honda Beat automatic motorbikes in Sananwetan District, Blitar City.